Regional disturbance predisposition assessment to support management in Norway spruce-dominated mountain forests - Leon J. Bührle; Tobias Kalt; Peter Bebi; Michaela Teich; Martina L. Hobi; Alexander Bast; Roman Schrott; Kevin Helzel; Christian Temperli; Leo G. Bont; Clemens Blattert; Janine Schweier; et al. (Forest Ecology and Management, 2026)

Growing trees decrease the frequency of avalanche release in an alpine afforestation in the Swiss Alps - Natalie Piazza; Alessandra Bottero; Johan Gaume; Giorgio Vacchiano; Marco Marcer; Peter Bebi (Cold Regions Science and Technology, 2025)

Resilience to late frost and drought of mixed forests with Turkey oak and silver fir in southern Italy - Concetta Lisella; Alessandra Bottero; Serena Antonucci; Giovanni Santopuoli; Roberto Tognetti (Forest Ecology and Management, 2025)

Assessing Ecosystem Services through a multimethodological approach based on multicriteria analysis and cost-benefits analysis: A case study in Turin (Italy) - Alessandra Oppio; Caterina Caprioli; Marta Dell’Ovo; Marta Bottero (Journal of Cleaner Production, 2024)

Post-windthrow forest development in spruce-dominated mountain forests in Central Europe - Natalie Piazza; Peter Bebi; Giorgio Vacchiano; Andreas Rigling; Thomas Wohlgemuth; Alessandra Bottero (Forest Ecology and Management, 2024)

Meta-analysis Reveals Different Competition Effects on Tree Growth Resistance and Resilience to Drought - Daniele Castagneri; Giorgio Vacchiano; Andrew Hacket-Pain; R. Justin DeRose; Tamir Klein; Alessandra Bottero (Ecosystems, 2022)
Drought will increasingly threaten forest ecosystems worldwide. Understanding how competition influences tree growth response to drought is essential for forest management aiming at climate change adaptation. However, published results from individual case studies are heterogeneous and sometimes contradictory. We reviewed 166 cases from the peer-reviewed literature to assess the influence of stand-level competition on tree growth response to drought. We monitored five indicators of tree growth response: mean sensitivity (inter-annual tree ring width variability); association between inter-annual growth variability and water availability; resistance; recovery; and resilience to drought. Vote counting did not indicate a consistent effect of competition on mean sensitivity. Conversely, higher competition for resources strengthened the association between water availability and inter-annual growth rates. Meta-analysis showed that higher competition reduced resistance ( p < 0.001) and improved recovery ( p < 0.05), but did not consistently affect resilience. Species, site and stand characteristics, and drought intensity were insignificant or poor predictors for the large variability among the investigated cases. Our review and meta-analysis show that competition does not affect the response of tree growth to drought in a unidirectional and universal way. Although density reduction (thinning) can alleviate growth declines during drought, the effects on growth after stress are uncertain. The large variability among investigated cases suggests that local-scale processes play a crucial role in determining such responses and should be explicitly evaluated and integrated into specific strategies for adaptation of forests to climate change.

Growth resistance and resilience of mixed silver fir and Norway spruce forests in central Europe: Contrasting responses to mild and severe droughts - Alessandra Bottero; David I. Forrester; Maxime Cailleret; Ulrich Kohnle; Arthur Gessler; Dominic Michel; Arun K. Bose; Jürgen Bauhus; Harald Bugmann; Matthias Cuntz; Loïc Gillerot; Marc Hanewinkel; et al. (Global Change Biology, 2021)
Extreme droughts are expected to increase in frequency and severity in many regions of the world, threatening multiple ecosystem services provided by forests. Effective strategies to adapt forests to such droughts require comprehensive information on the effects and importance of the factors influencing forest resistance and resilience. We used a unique combination of inventory and dendrochronological data from a long‐term (>30 years) silvicultural experiment in mixed silver fir and Norway spruce mountain forests along a temperature and precipitation gradient in southwestern Germany. We aimed at examining the mechanisms and forest stand characteristics underpinning the resistance and resilience to past mild and severe droughts. We found that (i) fir benefited from mild droughts and showed higher resistance (i.e., lower growth loss during drought) and resilience (i.e., faster return to pre‐drought growth levels) than spruce to all droughts; (ii) species identity determined mild drought responses while species interactions and management‐related factors strongly influenced the responses to severe droughts; (iii) intraspecific and interspecific interactions had contrasting effects on the two species, with spruce being less resistant to severe droughts when exposed to interaction with fir and beech; (iv) higher values of residual stand basal area following thinning were associated with lower resistance and resilience to severe droughts; and (v) larger trees were resilient to mild drought events but highly vulnerable to severe droughts. Our study provides an analytical approach for examining the effects of different factors on individual tree‐ and stand‐level drought response. The forests investigated here were to a certain extent resilient to mild droughts, and even benefited from such conditions, but were strongly affected by severe droughts. Lastly, negative effects of severe droughts can be reduced through modifying species composition, tree size distribution and stand density in mixed silver fir‐Norway spruce forests.

Tree Neighbourhood Diversity Has Negligible Effects on Drought Resilience of European Beech, Silver Fir and Norway Spruce - Loïc Gillerot; David I. Forrester; Alessandra Bottero; Andreas Rigling; Mathieu Lévesque (Ecosystems, 2021)

Growth and resilience responses of Scots pine to extreme droughts across Europe depend on predrought growth conditions - Arun K. Bose; Arthur Gessler; Andreas Bolte; Alessandra Bottero; Allan Buras; Maxime Cailleret; J. Julio Camarero; Matthias Haeni; Ana‐Maria Hereş; Andrea Hevia; Mathieu Lévesque; Juan C. Linares; et al. (Global Change Biology, 2020)
Global climate change is expected to further raise the frequency and severity of extreme events, such as droughts. The effects of extreme droughts on trees are difficult to disentangle given the inherent complexity of drought events (frequency, severity, duration, and timing during the growing season). Besides, drought effects might be modulated by trees’ phenotypic variability, which is, in turn, affected by long‐term local selective pressures and management legacies. Here we investigated the magnitude and the temporal changes of tree‐level resilience (i.e., resistance, recovery, and resilience) to extreme droughts. Moreover, we assessed the tree‐, site‐, and drought‐related factors and their interactions driving the tree‐level resilience to extreme droughts. We used a tree‐ring network of the widely distributed Scots pine ( Pinus sylvestris ) along a 2,800 km latitudinal gradient from southern Spain to northern Germany. We found that the resilience to extreme drought decreased in mid‐elevation and low productivity sites from 1980–1999 to 2000–2011 likely due to more frequent and severe droughts in the later period. Our study showed that the impact of drought on tree‐level resilience was not dependent on its latitudinal location, but rather on the type of sites trees were growing at and on their growth performances (i.e., magnitude and variability of growth) during the predrought period. We found significant interactive effects between drought duration and tree growth prior to drought, suggesting that Scots pine trees with higher magnitude and variability of growth in the long term are more vulnerable to long and severe droughts. Moreover, our results indicate that Scots pine trees that experienced more frequent droughts over the long‐term were less resistant to extreme droughts. We, therefore, conclude that the physiological resilience to extreme droughts might be constrained by their growth prior to drought, and that more frequent and longer drought periods may overstrain their potential for acclimation.

Contrasting resistance and resilience to extreme drought and late spring frost in five major European tree species - Yann Vitasse; Alessandra Bottero; Maxime Cailleret; Christof Bigler; Patrick Fonti; Arthur Gessler; Mathieu Lévesque; Brigitte Rohner; Pascale Weber; Andreas Rigling; Thomas Wohlgemuth (Global Change Biology, 2019)
Extreme climate events (ECEs) such as severe droughts, heat waves, and late spring frosts are rare but exert a paramount role in shaping tree species distributions. The frequency of such ECEs is expected to increase with climate warming, threatening the sustainability of temperate forests. Here, we analyzed 2,844 tree‐ring width series of five dominant European tree species from 104 Swiss sites ranging from 400 to 2,200 m a.s.l. for the period 1930–2016. We found that (a) the broadleaved oak and beech are sensitive to late frosts that strongly reduce current year growth; however, tree growth is highly resilient and fully recovers within 2 years; (b) radial growth of the conifers larch and spruce is strongly and enduringly reduced by spring droughts—these species are the least resistant and resilient to droughts; (c) oak, silver fir, and to a lower extent beech, show higher resistance and resilience to spring droughts and seem therefore better adapted to the future climate. Our results allow a robust comparison of the tree growth responses to drought and spring frost across large climatic gradients and provide striking evidence that the growth of some of the most abundant and economically important European tree species will be increasingly limited by climate warming. These results could serve for supporting species selection to maintain the sustainability of forest ecosystem services under the expected increase in ECEs.

What is the potential of silver fir to thrive under warmer and drier climate? - Yann Vitasse; Alessandra Bottero; Martine Rebetez; Marco Conedera; Sabine Augustin; Peter Brang; Willy Tinner (European Journal of Forest Research, 2019)

Multiplex primer-extension assay for identification of Yersinia species - Alessandra Dalmasso; Tiziana Civera; Virginia Filipello; Maria Teresa Bottero (Molecular Biology Reports, 2014)

Degenerative myelopathy in German Shepherd Dog: comparison of two molecular assays for the identification of the SOD1:c.118G>A mutation - Maria Teresa Capucchio; Veronica Spalenza; Elena Biasibetti; Maria Teresa Bottero; Roberto Rasero; Alessandra Dalmasso; Paola Sacchi (Molecular Biology Reports, 2014)